Freshwater transport variation through Fram and Davis Strait influenced by atmospheric circulation - Zhang, Jinlong; Du, Ling (Frontiers in Marine Science, 2025)
With global warming, the freshwater content in the Arctic Ocean has been steadily accumulating since the 21st century, which causes notable alterations in the export of freshwater from the Arctic Ocean. This paper presents a comparative analysis of the variations in liquid freshwater transport (FWT) through Fram Strait and Davis Strait, the primary export pathways of the Arctic freshwater, spanning from 1980 to 2023. We also use reanalysis data, combined with atmospheric and sea ice data, to explore the impact of atmospheric circulation anomaly and the distribution of freshwater content in the Arctic Ocean on FWT in the straits. The research findings reveal that over the past four decades, the FWT through the straits has not exhibited the anticipated continuous growth. Instead, we observed distinct temporal shifts in regional freshwater export patterns: The FWT in Fram Strait experienced significant increase prior to the 21st century (trend of 10.14 mSv/10yr during 1980-2000), whereas the FWT in Davis Strait showed acceleration after 2000 (trend of 13.69 mSv/10yr). There are significant interannual variations in the FWT in both straits, which are linked to the intensity of Atlantic inflow in the straits. Large scale circulation has a direct impact on FWT in straits, but there are significant regional differences. In the positive phase of the Arctic Oscillation (North Atlantic Oscillation) and the negative phase of the Dipole Anomaly, the cyclonic circulation anomaly in the Arctic Ocean favors enhanced surface outflow on both sides of Greenland. This, coupled with the storage of freshwater content in the margin of Greenland, leads to an intensification of the freshwater export through the Davis Strait. The FWT through the Fram Strait remains uncertain due to conflicting trends of increased outflow and decreased freshwater content. It can be determined that the FWT in Fram Strait is related to the upstream FWC, buffered by the accumulation of freshwater in northern Greenland. Furthermore, the ongoing Atlantic inflow warming against the backdrop of the Atlantic Multidecadal Oscillation phase transition results in sea ice melting in the Arctic Ocean in the long term, thereby increasing the freshwater content on both sides of Greenland and tending to boost the freshwater export through the straits.